RENCANA KAMPUNG TEMATIK KELURAHAN CIKARET KOTA BOGOR BERBASIS KOMUNITAS - Rahmat Rejoni; Andrianto Kusumoarto (Lakar: Jurnal Arsitektur, 2020)
One of the areas and spaces in a city is the urban village area which is located almost spread in all urban areas and is generally dominated by residential areas with generally high settlement densities. This area is an inseparable part of an urban area and its physical form and order must be harmonized with the city, and at the same time it must also have a level of community welfare that is also in harmony and can support the level of welfare of the city. In order to improve the quality of society and the environment in Bogor City as desired by the Bogor City government, in 2017 an innovative thematic village idea contest was held. In order to implement the results of this innovative thematic village idea competition, a Landscape Design Plan for 7 (seven) villages with the highest value was carried out. One of them is KAMPUNG SEMUT KROTO Area, Cikaret Village, South Bogor District. Through the program of community service activities Indraprasta University PGRI Jakarta Faculty of Computer Science Engineering Department majoring in Architecture will collaborate with the village of Cikaret to organize the thematic tourist village. Community service with thematic village planning in the Cikaret sub-district will offer solutions to make Thematic village design concept drafts and make Thematic village design engineering details.